Trace H2O2‐Assisted High‐Capacity Tungsten Oxide Electrochromic Batteries with Ultrafast Charging in Seconds. Issue 25 (9th May 2016) - Zhao, Jinxiong; Tian, Yuyu; Wang, Zhen; Cong, Shan; Zhou, Di; Zhang, Qingzhu; Yang, Mei; Zhang, Weikun; Geng, Fengxia; Zhao, Zhigang
Abstract: A recent technological trend in the field of electrochemical energy storage is to integrate energy storage and electrochromism functions in one smart device, which can establish efficient user–device interactions based on a friendly human‐readable output. This type of newly born energy storage technology has drawn tremendous attention. However, there is still plenty of room for technological and material innovation, which would allow advancement of the research field. A prototype Al‐tungsten oxide electrochromic battery with interactive color‐changing behavior is reported. With the assistance of trace amount of H2 O2, the battery exhibits a specific capacity almost seven times that for the reported electrochromic batteries, up to 429 mAh g −1 . Fast decoloration of the reduced tungsten oxide affords a very quick charging time of only eight seconds, which possibly comes from an intricate combination of structure and valence state changes of tungsten oxide. This unique combination of features may further advance the development of smart energy storage devices with suitability for user–device interactions. Abstract : A high‐performance electrochromic battery with unprecedented charging time down to eight seconds and specific capacity up to 429 mAh g −1 was designed, in which the level of energy stored can be constantly and visually conveyed by recognizing variations in color. The high capacity may come from an intricate combination of structure and valence state changes of the tungsten oxide electrode.